Raja Ali Haji dan Hang Tuah: Arloji dan Mufassar - Hendrik M.J. Maier, (Universiti Kebangsaan Malaysia, 2001)
Little is known of those who created, wrote and copied texts in Malay before 1900. The famous author of Tuhfat al-Nafis, Raja Ali Haji, is one of the first Malay writers who we know more about, thanks to the publications of what is left of his personal correspondence with the German born scholar, Von de Wall between 1855 and 1870. The letters make us possible to construct a picture of Raja Ali Haji as an individual, a worried man tormented by many problems and issues of his day. This picture could help us to develop a better understanding of his writings